Hubungan Pengetahuan dan Motivasi Wanita Usia Subur Dengan Deteksi Dini Kanker Serviks di Puskesmas Payo Selincah Kota Jambi Tahun 2020 - Silitonga, Sondang; Aguspairi, Aguspairi (Universitasdiwangsa Jambi, 2021)
In Indonesia, approximately 15000 new cases of cervix cancer happened every year, while there are approximately 7500 deaths every year. Indonesian women awareness of IVA test and its important as initial screening for cervix cancer are still quite low (5%), therefore there are still many cervix cancer cases that were found in late stages. This study used an analytic method with a cross-sectional approach and accidental sampling with purpose to find out the relationship between knowledge and motivation of women of reproductive age with early detection of cervix cancer in Puskesmas Payo Selincah Kota Jambi (Payo Selincah Public Health Center) in 2020. This study was conducted in Puskesmas Payo Selincah Kota Jambi (Payo Selincah Public Health Center). Study result showed a significant relationship between between knowledge and motivation of women of reproductive age with early detection of cervix cancer in Puskesmas Payo Selincah Kota Jambi (Payo Selincah Public Health Center) with respectively p value 0.003 and 0.021. From this study we suggest for public health stakeholder and public health center to put more attention to raise awareness of the important of early detection of cervix cancer for women of reproductive age.